Modern criteria for demarcated mental norm and mental pathology - N. A. Kosenko; G. T. Krasilnikov; V. G. Kosenko; M. I. Ageev; L. M. Shulkin; Y. V. Gridina; S. A. Farafontov; E. K. Tsagaraeva (Кубанский научный медицинский вестник)
The article describes the complexity of modern theoretical and practical approaches to the understanding of mental health and disease. Nozotsentrichesky and normotsentrichesky approaches are analyzed. The possibility of the use of general medical criteria dichotomy «norm/pathology» is discussed. From the standpoint of the modern paradigm of biopsychosocial unity of man analyzes the specificity criteria of mental norms of social and ethnocultural conditions. It describes the current criteria for the analysis - the presumption of mental health.